The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00198-011-1890-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone microarchitecture by high-resolution peripheral quantitative computed tomography (HR-pQCT) in hemodialysis patients

Abstract: We conclude that hemodialysis patients have a marked decreased in cortical density, thickness, and area with significant reduction in trabecular parameters that correlated with the severity of secondary hyperparathyroidism only in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 34 publications
7
30
0
Order By: Relevance
“…By integrating all microstructural variables, FEA-determined bone strength might be a more valid outcome to study the consequences of ESRD on bone than isolated variables. These results are similar to two recent publications [14,15] and do not support the hypothesis of a selective cortical bone deficit in dialysis patients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…By integrating all microstructural variables, FEA-determined bone strength might be a more valid outcome to study the consequences of ESRD on bone than isolated variables. These results are similar to two recent publications [14,15] and do not support the hypothesis of a selective cortical bone deficit in dialysis patients.…”
Section: Discussionsupporting
confidence: 85%
“…This variable was more predictive than any HR-pQCT parameter, and the addition of HR-pQCT results to ultradistal radius aBMD did not improve fracture discrimination [11]. In dialysis patients, Negri et al [14] found a marked decrease in cortical density, thickness, and area, together with reductions in trabecular parameters in both men and women. However, these changes correlated with the severity of secondary hyperparathyroidism in women only.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…All aspects of bone microstructure were altered in HIV+ve successfully treated premenopausal women. The evaluation of bone microstructure changes using the same technique in hemodialysis patients has shown relative changes to a similar extent in both radius and tibia sites (29 % reduction in total and trabecular density with a trabecular number reduced by 25 %) [30]. Our findings raise certain questions.…”
Section: Discussionmentioning
confidence: 51%
“…Biochemical (calcium, phosphate, parathyroid hormone [PTH] and vitamin D) and bone abnormalities (renal osteodystrophy) complicating advanced CKD and dialysis are associated with significant morbidity and mortality (1)(2)(3)(4)(5)(6), probably due to greater risk of fracture and extra-skeletal calcification leading to cardiovascular disease (7)(8)(9). Severe SHPT in dialysis patients is associated with up to 20% increased mortality (4,5) and dialysis patients also have up to four fold increase in fracture incidence compared to non-dialysis patients (10) due to impaired bone quality (11,12). Vascular calcification is highly prevalent in CKD and is only weakly related to traditional risk factors of cardiovascular disease in the general population such as hypertension and hyperlipidaemia (13).…”
Section: Introductionmentioning
confidence: 99%